Community worker perceptions of the Income Management regime in Shepparton. Issue 4 (December 2016) - Banks, Marcus; Tennant, David
Abstract : This paper focuses on how community workers in Shepparton viewed the impact of the Place Based Income Management (PBIM) trial on the lives of their clients, their clients' families, and the broader community. The paper responds to criticism that there has been a lack of community voices in the development of PBIM or of their inclusion in the formal evaluation framework, raised in Philip Mendes's 2013 study of this trial site. A key policy goal underlying Income Management is that the tool assists low income people to become better money managers. Our study found that Shepparton community workers also used the parlance of 'tool' to describe the programmatic value of the BasicsCard in their interactions with clients. However, the BasicsCard appeared marginal to their discussions. Three clear themes emerged from the interviews: Shepparton's focus on voluntary clients, and ascertaining why participation in the local trial had dropped; that support for IM centred on the voluntary measure and the extra resources available to assist clients; and pragmatically locating the program in the middle of a welfare continuum that stretched from the voluntary Centrepay at one end to the highly coercive and restrictive paternalism of State Trustees at the other.